Hubungan Antara Motivasi Berprestasi Dengan Kinerja Guru Agama Hindu Jenjang Sekolah Dasar - I Made Wiguna Yasa; I Komang Wisnu Budi Wijaya; I Gede Sudha Cahyana (Jayapangus Press, 2021)
This research aims to describe the relationship between the achievement motivation and the performance of Hindu religious teachers at elementary school levels who have not been certified as educators. This research is classified as a correlational research. The population of this study were teachers of Hindu religion in elementary schools in Tabanan Regency who had not been certified as educators. The sampling technique used was saturated sampling technique, in which all members of the population were sampled. The research instrument used was an observation sheet of achievement motivation and teacher performance. The data that has been collected were analyzed descriptively and also analyzed by inferential statistics. The analysis of statistic inferential was using a product moment correlation with significant level of 0.05. The result states that: 1) there is a significant relationship between the achievement motivation and the performance of Hindu religious teachers at elementary school levels who have not been certified as educators (sig < 0,05) and 2) The closeness level of the relationship between achievement motivation and teacher performance is classified as strong (rxy = 0,715).